Assessing the Impact of Kitchen Nightmares through TripAdvisor - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (The Platformisation of Consumer Culture, 2024)
Drawing on 5,608 customer ratings and reviews scraped from TripAdvisor, the chapter assesses how the restaurants appearing on Kitchen Nightmares Italy are doing after the airing of the show. Based on ad hoc statistical analysis of reviews and rating scores, we observe that the show has a very limited impact on the restaurants' visibility, reputation, and quality on TripAdvisor; reviews do have a boost thanks to Kitchen Nightmares, but only in conjunction with the airing of the show. However, scores are disconnected from the programme airing date, and display a paradoxical relationship with reviews: the more the reviews, the lesser the score. Finally, through a qualitative analysis of customers' reviews, we highlight a particular tension, namely, that, on the one hand, the show enhances the restaurant's conditions while, on the other hand, it sets high expectations for both customers and restaurant owners.